2011
DOI: 10.1021/jf2025456
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drying and Storage on Lipid and Carotenoid Stability of the Microalga Phaeodactylum tricornutum

Abstract: The influence of short-term storage and spray- and freeze-drying of fresh microalgal paste on the stability of lipids and carotenoids of Phaeodactylum tricornutum was investigated. Furthermore, the effects of storage time (14 and 35 days) and condition (vacuum packed vs non vacuum packed, -20 °C vs 4 °C vs 20 °C) after spray- and freeze-drying were studied. Total lipid content, free fatty acid content, carotenoid content and degree of lipid oxidation were measured. No effects of spray- and freeze-drying and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 22 publications
5
68
0
9
Order By: Relevance
“…They found that oven-drying gives better results and is more suitable compared with freeze-drying in terms of protein extractability and protein digestion, as it is well presented in Table 8. Ryckebosch et al [34] explored and compared the influence of spray drying and freeze-drying on the lipid compound on phaeodactylum triconutum alga. The results presented in Fig.…”
Section: Comparison Of the Different Drying Methodsmentioning
confidence: 99%
“…They found that oven-drying gives better results and is more suitable compared with freeze-drying in terms of protein extractability and protein digestion, as it is well presented in Table 8. Ryckebosch et al [34] explored and compared the influence of spray drying and freeze-drying on the lipid compound on phaeodactylum triconutum alga. The results presented in Fig.…”
Section: Comparison Of the Different Drying Methodsmentioning
confidence: 99%
“…Solar drying can cause considerable denaturisation of organic compounds in seaweed [130][131][132][133]. Freeze drying tends to cause less damage to organic materials, but is more expensive than solar or conventional drying, and is typically used for products such as premium instant coffee to give better flavour [134,135].…”
Section: Dryingmentioning
confidence: 99%
“…Freeze drying tends to cause less damage to organic materials, but is more expensive than solar or conventional drying, and is typically used for products such as premium instant coffee to give better flavour [134,135]. Freeze drying has been used for algae, particularly microalgae, such as Dunaliella, but is considered too expensive for the large-scale commercial recovery of algae, and its use is confined primarily to research and some high-value seaweed products [132,133,136,137].…”
Section: Dryingmentioning
confidence: 99%
“…Além de reduzir a atividade de água até um nível em que o crescimento microbiano e reações de deterioração são minimizados, a secagem reduz custos de transporte, embalagem e de armazenamento (VegaGálvez et al, 2011). A secagem de microalgas tem sido realizada em secadores de bandeja (Oliveira et al, 2010), spray dryer, freeze-dryer (Ryckebosch et al, 2011), leito de jorro (Oliveira et al, 2008) e secagem solar. Estudos utilizando secagem a vácuo em microalgas ainda não foram reportados na literatura.…”
Section: Introductionunclassified